Public Service Motivation and Turnover Intention: Testing the Mediating Effects of Job Attitudes - Gan, Kai-Peng; Lin, Yun; Wang, Qiu (Frontiers in Psychology, 2020)
Research on the role of public service motivation (PSM) relating to work performance has been a significant topic in recent years, however, the relationship between PSM and job performance remains mixed. To investigate whether job attitudes mediate the effect of PSM on public employees’ turnover intention, this study integrated job satisfaction and organizational commitment into a single model. Based on a sample of 587 full-time Chinese public employees, our findings revealed that job satisfaction and organizational commitment respectively mediated the negative association between PSM and employees’ turnover intention. Multiple mediation analysis indicated that job satisfaction and organizational commitment sequentially mediated the effects of PSM on turnover intention. As a result, our findings suggested that public employees with high PSM levels preferred to stay in the public organizations. The theoretical and practical implications of our findings are discussed.